Alkotmányreformok Olaszországban 2000-től - Drinóczi, Tímea (Debreceni Jogi Műhely, 2008)
The paper deals with the constitutional reforms that has been taken place in Italy since 2000. It enumerates all of the constitutional amandements according to their subject matter. The first issue is the modification affecting the right to vote; the second one concerns the right to equality in the field of public affairs; the third amandement modifies some transitional provisions; the fourth is about the reform of Title V of the Constitution regulating the regions and local governments; an the last one specifies the failed constitutional reform that would have changed the basis of the recent governmental system of Italy.